2022
DOI: 10.3390/ani12060693
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Tools for Analysis of Single-Nucleotide Polymorphisms in the Bovine Transferrin Gene

Abstract: Dairy cattle with a high milk yield are susceptible to many infectious diseases, such as mastitis. Subclinical mastitis (SCM) is the most prevalent form of mastitis that predominantly affects animal health, and causes adverse effects on the quality and quantity of milk. In dairy animals, subclinical mastitis often remains undetected, as no gross changes in udder characteristics are visible. In the present study, 135 Holstein Friesian dairy animals were selected and screened as healthy (n = 25) and mastitic (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… Ben Meir et al (2022) found that transferrin is a differentially expressed protein in mid-lactation cows through proteomics, which is upregulated in eight Fe-related pathways and can be used as a candidate biomarker. Three SNPs of transferrin were detected in a recent study ( Ali et al, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“… Ben Meir et al (2022) found that transferrin is a differentially expressed protein in mid-lactation cows through proteomics, which is upregulated in eight Fe-related pathways and can be used as a candidate biomarker. Three SNPs of transferrin were detected in a recent study ( Ali et al, 2022 ).…”
Section: Resultsmentioning
confidence: 95%
“…SIFT was initially utilized for human studies including cancer. Now, its use has been extended several animal species such cattle (Ali et al, 2022) [16] , canines (Gharahkhani et al, 2011) [17] . Further verification of harmful effect of mutation was performed using software PolyPhen-2 software (Adzhubei et al, 2010) [20] .…”
Section: Prediction Of Deleterious Nssnpsmentioning
confidence: 99%
“…The fundamental limitation of this study is that most computational methods utilised were optimised for the human genome. However, similar computational techniques have been successfully used for in silico analysis of SNPs in non-human species [67][68][69]. In vitro analysis, for example, site-directed mutagenesis, is recommended for future studies to validate the impacts of these nsSNPs, particularly for c.1271C>T (P424L).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%